2015
DOI: 10.1007/s00267-015-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

More of the Same: High Functional Redundancy in Stream Fish Assemblages from Tropical Agroecosystems

Abstract: In this study, we investigated the influence of environmental variables (predictor variables) on the species richness, species diversity, functional diversity, and functional redundancy (response variables) of stream fish assemblages in an agroecosystem that harbor a gradient of degradation. We hypothesized that, despite presenting high richness or diversity in some occasions, fish communities will be more functionally redundant with stream degradation. Species richness, species diversity, and functional redun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 64 publications
(73 reference statements)
6
76
2
4
Order By: Relevance
“…In tropical streams, although studies about scale-related effects are still scarce, the findings are similar to those of temperate environments. For example, in tropical agricultural landscapes both catchment-and local-scale features affected both functional and taxonomic diversity of stream fish communities (Cruz et al 2013;Bordignon et al 2015;Santos et al 2015; but see Casatti et al 2015). However, it should be mentioned that although catchment variables are important (Roth et al 1996), in most cases local-scale variables accounted for the most variation in fish community structure (Lammert & Allan 1999;Wang et al 2003;Diana et al 2006;Johnson et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In tropical streams, although studies about scale-related effects are still scarce, the findings are similar to those of temperate environments. For example, in tropical agricultural landscapes both catchment-and local-scale features affected both functional and taxonomic diversity of stream fish communities (Cruz et al 2013;Bordignon et al 2015;Santos et al 2015; but see Casatti et al 2015). However, it should be mentioned that although catchment variables are important (Roth et al 1996), in most cases local-scale variables accounted for the most variation in fish community structure (Lammert & Allan 1999;Wang et al 2003;Diana et al 2006;Johnson et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…homogeneous landscape) is not able to overcome the impact of local-scale variables (Heino et al 2007;Casatti et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, higher values of food niche overlap (H') and of community specialization (H 2 ) (Table 2) were observed in the forested stretch. Although some authors (Agostinho et al, 2008;Zeni and Casatti, 2014) relate impacted environments with habitat simplification and homogenization, which would reduce the food resources supply to the fish fauna, Casatti et al (2015) discuss that the presence of grass on the banks in pasture streams provides food resources such as leaves and roots and also retains organic matter. Moreover, they may also provide additional microhabitats used by macroinvertebrates that may serve as food for the fish fauna.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Casatti et al (2015) have found that although environments without riparian vegetation may have higher richness and diversity of fish, they also have a high functional redundancy, mostly related to feeding. Those impacted environments are generally simpler, with high habitat homogenization and low allochthonous resources supply (Zeni and Casatti, 2014).…”
Section: Introductionmentioning
confidence: 99%